Characteristics of Ultramafic Igneous Rock Ofiolite Complex in Asera District, North Konawe Regency Southeast Sulawesi Province, Indonesia - Hasria; Erzam S. Hasan; Deniyatno; L M Iradat Salihin; Asdiwan (UIR PRESS, 2020)
The research area is located in Asera District, North Konawe Regency, Southeast Sulawesi Province which has ultramafic rock lithology. The purpose of this study is to determine the characteristics of ultramafic igneous rocks using petrographic and geochemical analysis. Petrographic analysis aims to determine the types and abundance of minerals present so that rock types can be determined based on the classification of Travis (1955) and Streckeisen (1976). The geochemical analysis aims to determine the oxide/major element so that it can determine the type of magma based on the AFM classification according to Irvine and Baragar (1971) and the origin of the magma / original rock formation environment based on Pearce (1977). Petrographic analysis results showed that ultramafic rocks in the study area consisted of 2 types of rocks namely peridotite consisting of wherlit and lherzoite and serpentinite. The results of geochemical analysis indicate that the type of magma in the study area is thoellitic series and the origin of the magma/rock formation environment comes from the expansion of the oceanic floor or mid oceanig ridge (MOR) which is ultramafic.